Arbeitsmarkt 2030 - Digitalisierung der Arbeitswelt Fachexpertisen zur Prognose 2016 - Düll, Nicola (W. Bertelsmann Verlag, 2016)
The analyses and results included in the technical assessment complement the third main study "The German Labour Market in 2030 - Economy and Labour Market in the Digital Age - Forecast 2016" (Original title: Arbeitsmarkt 2030 - Wirtschaft und Arbeitsmarkt im digitalen Zeitalter; Prognose 2016). The authors examine the implications of digitalisation on today's work by means of different individual assessments, taking into account economic, sociological and organisational aspects. Moreover, they provide an overview of existing or planned measures to support digitalisation.